A therapeutic group program in an aged person’s mental health unit - George, Kuruvilla; Ferris, Angela (International Journal of Medicine, 2013)
Objective: The aim of this paper is to describe a therapeutic group program in an acute aged person’s mental health inpatient unit. The setting of the unit, the development of the program and patient feedback are discussed. Conclusion: The key factor in the success of the group program was the support of the multidisciplinary staff facilitators of the program. An ongoing and significant challenge is the provision of groups appropriate for the varying levels of function within the patient group and especially meeting the needs of patients with behavioural and psychological symptoms of dementia